2020
DOI: 10.3389/fphys.2020.00095
|View full text |Cite
|
Sign up to set email alerts
|

Bogong Moths Are Well Camouflaged by Effectively Decolourized Wing Scales

Abstract: Moth wings are densely covered by wing scales that are assumed to specifically function to camouflage nocturnally active species during day time. Generally, moth wing scales are built according to the basic lepidopteran Bauplan, where the upper lamina consists of an array of parallel ridges and the lower lamina is a thin plane. The lower lamina hence acts as a thin film reflector having distinct reflectance spectra that can make the owner colorful and thus conspicuous for predators. Most moth species therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“… Stavenga et al, 2014b ). The scales become brown with moderate amounts of melanin, which is the case in most moths ( Stavenga et al, 2020 ). Yet, Mason (1927) noticed that a primitive moth, a washed purple Eriocrania sp., had scales colored by their basal membrane that ‘behaves as if it were a single thin film’, but he found that the reflection color (purplish to orange) was relatively faint.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… Stavenga et al, 2014b ). The scales become brown with moderate amounts of melanin, which is the case in most moths ( Stavenga et al, 2020 ). Yet, Mason (1927) noticed that a primitive moth, a washed purple Eriocrania sp., had scales colored by their basal membrane that ‘behaves as if it were a single thin film’, but he found that the reflection color (purplish to orange) was relatively faint.…”
Section: Discussionmentioning
confidence: 92%
“…The melanin thus effectively blocks the lower lamina twofold, as only a small fraction of incident light reaches the lower lamina and even much less of the light reflected by the lower lamina then passes the upper lamina at the way back (e.g., Stavenga et al, 2014b). The scales become brown with moderate amounts of melanin, which is the case in most moths (Stavenga et al, 2020). Yet, Mason noticed that a primitive moth, a…”
Section: Discussionmentioning
confidence: 99%
“…Melanin is the signi cant factor in uencing the brown scales ultrastructure and response of our model. Moths' wings are usually dull as a consequence of high melanin content in brown or dark scales 25 . The same we can state on brown melanin-pigmented scales on Diachrysia wings.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies refer to spectral properties of butter ies and moths but most of them have considered only re ectance in human-visible wavelengths (380-780 nm) in which coloration is perceivable. The color of the wing can be pigment-dependent and a separate phenomenon is the structural colors of the wing, which was the subject of in-depth research conducted also on the Noctuidae family [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Such markings also generally appear on the dorsal side of the wings, meaning that ground-based remote sensing technology has a limited ability to probe such spectral features [ 26 ]. The ventral sides of moth wings exhibit shades of brown [ 27 ], which is somewhat discouraging in terms of the potential for differentiating moth species remotely. The scattering phase function (the so-called bidirectional reflectance distribution function (BRDF)) recorded from the majority of moths displays a diffuse and Lambertian behaviour [ 28 ].…”
Section: Introductionmentioning
confidence: 99%